OPTIMASI VIDEO STREAMING DART SERVER KE CLIENT PADA JARINGAN BLUETOOTH PICONET PERVASIVE - Hasad, Andi (JREC (Journal of Electrical and Electronics), 2012)
The objective of this research is to develop a piconet pervasive system by performingthe optimization and analysis of video streaming on the network by utilizing the bluetooth cell phones and computers media in an condition which have Wi-Fi or do not have Wi-Fi. Stages of research include : analysis of bluetooth network system, design a prototype system, audio video compression, hint track, optimization, system testing,performance measurement, and analysis of measurement results. The results obtained from measurements of packet loss value for all video compression on a client-server distance of 10 m has been fulfilling the Ciscostandard of QoS video streaming, where the smallest value obtained at 8 kbps data rate of4.38%packet loss to an condition that does not have Wi-Fi, and a distance of client - server 10 m. In condition that have Wi-Fi signal strength of-78 dBm, the smallest value obtained of 4.64%packet loss. Throughput and delay parameters of the video compression meets the QoS of video streaming in which the delay have values ranged from 0.62 - 1.81 milliseconds, while the standard of maximum delay for QoS video streaming is 5 seconds. The results showed a video streaming system that meets the Cisco standard for QoS video streaming value of the throughput, delay, jitter and packet loss.Keywords: video streaming, bluetooth, optimization, client-server, piconet pervasive